Протидія нелегальній міграції: міжнародний досвід - Звьоздная, Т. М.; Звездная, Т. М.; Zvezdnaja, Т. (My University, 2012)
Foreign experience of counteraction of illegal migration is investigated in the article, a modern legislation, seriousness of problem of fi ght against illegal migration and infl uence of this phenomenon, is illuminated on a law and order not only in separate countries but also in the world.
Звьоздная Т. М. Протидія нелегальній міграції: міжнародний досвід /Т. М. Звьоздная // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 45. – С. 130-137.
Keywords: нелегальна міграція; боротьба з нелегальною міграцією; іноземний досвід протидії нелегальній міграції; нелегальная миграция; борьба с нелегальной миграцией; иностранный опыт противодействия нелегальной миграции; illegal migration; fight against illegal migration; foreign experience in combating illegal migration